Assessing the impact of agri-environmental payments on green productivity in Germany - Ait Sidhoum, Amer; Mennig, Philipp; Frick, Fabian (Elsevier, 2024)
This study offers a novel empirical application for assessing the impact of agri-environment schemes (AES) on the performance of farms. The existing evidence about the impact of these schemes considering environmental and economic aspects equally is still limited. Therefore, our objective is to contribute to the literature on the impact evaluation of AES by considering three important aspects in our empirical analysis. First, the performance of farms is proxied by an indicator that incorporates environmental externalities into production activities. Second, our empirical analysis focuses on a sample of Bavarian dairy farms covering the period 2013–2018, thus, we can evaluate the effectiveness of agri-environmental schemes in one of Germany's leading agricultural and forestry regions during the latest programming period. Finally, in an effort to increase robustness, we employ an improved version of the Malmquist-Luenberger productivity index, which enables us to get around some of the shortcomings of the original index. The obtained results suggest that agri-environment payments have a limited effect on improving farm-level green productivity.
Keywords: Agri-environment schemes; Policy evaluation; Green productivity; Data envelopment analysis